The relationship between objectively measured physical activity and fundamental motor skills in 8 to 11 years old children from the Czech Republic - Balaban, V. (Montenegrin Journal of Sports Science and Medicine, 2018)
The aim of this research was to explore the relationship between objectively measured physical activity and fundamental motor skills in 8-to-11-year-old children from the Czech Republic. The research sample consisted of 201 children (108 boys and 93 girls) aged 8-11 from Olomouc, Czech Republic. The Test of Gross Motor Development 2 was used to assess the level of children`s fundamental motor skills. Furthermore, an ActiGraph GTX3 device accelerometer was used for the objective measurement of physical activity levels. The results have shown a low-to-medium correlation between moderate to vigorous physical activity and locomotor motor skills among the total sample, as well as between vigorous physical activity and object control skills in the sample of boys. Fundamental motor skills are essential factors for children`s participation in organized and free-time physical activities. There is a commitment to develop fundamental motor skills in children, especially object control motor skills in girls.